Orodispersible Tablets: A splendid Form of Oral Drug Delivery System- An Updated Review - Kumar, Ritesh (International Journal of Pharmaceutical & Biological Archive, 2016)
Orodispersible tablets (ODTs) are solid dosage forms that disintegrate or dissolve in the oral cavity in less than 60 seconds without water and chewing. They were first introduced to the market in the 1980s, and become one of the fastest growing subdivisions of the oral drug delivery industry and their products are developing at a great rate. New orodispersible tablet technologies address many pharmaceutical and need of patients, ranging from enhanced life-cycle management for suitable dosing for pediatric, geriatric and psychiatric patients with dysphagia. This is seen to affect about 35% of the general population and associated with a number of diseases like Parkinsonism, mental disability, motion sickness, unconsciousness, water unavailability etc. Other groups that may face problems using conventional oral dosage forms include the mentally ill, the partially developed patients, and some patients who are uncooperative, on reduced liquid intake, or are nauseated. To overcome such difficulties, orodispersible tablets have been developed. This property in dosage form can be reached by the addition of different excipients, from which super disintegrant is the key adjuvant. This has motivated both academia and industry to generate new orally dispersible formulations and technological approaches in the field. Among the dosage forms developed to facilitate for easy medication, the Orodispersible tablets (ODTs) are one of the most widely implemented commercial products. The aim of this review article is to give knowledge of desired characteristics, advantages, preparation methodologies, patented technologies, evaluation and industrial applications of ODTs formulation.